Family Finansial Planning Strategy Fishermen in Sibolga City Central Tapanuli - Ahmad Sayuti Pulungan; Yusuf Pathuansyah; Rizky Mery Octavianna Lubis (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The fishermen face two seasons, namely the fish harvest season and the famine season, where these two seasons greatly affect the income earned by fishermen. In the fish harvest season, fishermen earn relatively large incomes, while in the lean season, fishermen earn relatively little income so that fishermen need to have a strategy in carrying out family financial planning. The purpose of this study was to analyze the financial planning strategies of fishermen's families during the lean season and the fish harvest season. This study uses descriptive qualitative research methods with the number of research respondents of 10 fishermen in sibolga and data collection techniques through in-depth interviews. The results showed that during the fish harvest season, the family's financial planning strategy was to save and serve as business capital. Meanwhile, during the family season, the family's financial planning strategy is a coping strategy by reducing daily expenses and increasing income.